Analysıs Of The Role Of Multısensory Methods In Learnıng Javanese Scrıpt In Class Iv Prımary Schools In Banyuwangı Cıty - Wardani, Rizky Okta; Soenaryo, Siti Fatimah; Suwandayani, Beti Istanti (Elementary Teacher Education Program, Majalengka University, 2024)
The preservation of local cultural heritage is one of the essential things that need to be considered in developing the character of the younger generation. In Indonesia, regional cultures are very varied and rich in values that are aesthetic and provide education. Local culture includes traditions, arts, customs, languages, and handicraft products that reflect the identity of a region. However, with globalization and technological advances, attention to preserving local culture is declining, especially among the youth. One way to overcome this problem is to integrate local culture into the teaching and learning process at school. Every grade 3 elementary school student must master Javanese writing and language skills. Most students find the skill of writing Javanese script very difficult to master. Learning to write Javanese scripts in elementary school needs to be studied to determine the teacher's teaching method in class. This study aims to analyze the ability of students to recognize, write, and read Javanese script letters after applying multisensory methods and describe the process of applying multisensory methods in learning Javanese script in class IV elementary school. This study uses descriptive qualitative research methods with data collection through observation, interviews, documentation, and research subjects, namely grade IV students and class teachers. The teacher uses the multisensory method, which involves using various senses in the learning process. The study results are expected to help other researchers compile Javanese language research, add insight into knowledge for readers in the field of education, and can be applied practically in the classroom as a form of learning.